ASPEK-ASPEK PENDIDIKAN DALAM AL-QUR’AN : Analisis Surat-Surat Makkiyah - Khotimah, Siti; Junariah, Siti; Juariah, Siti; Kamaria, Sitti; Komariyah, Siti; Khotijah, Siti (STAI Darul Qalam Tangerang, 2025)
Holy Quran is a Muslim orientation as Kalamullah (Allah saying), whose the truth is absolute. Holy Quran also applies in all day life and contains the education and guidance about everything related with human life in this world and hereafter. Holy Quran’s education and guidance relates with any concepts needed by human in sailing through their life. Several concepts as guidance, had written in Holy Quran such as Islamic law, science, faith, unity of God (Tauhid), behavior and others. In addition, the holy Quran educates us about the important education in order to achieve insan kamil who have high position in the world and hereafter. As explained that holy Quran contains any aspects of Islamic education and concept which can be a reference of Islamic education material. Holy Quran has an important Tauhid (unity of God) aspect to be learned, because it is the main point of Muslim’s belief. In addition, the education of behavior is also important for all of us. If human has not a good behavior, the world will be damaged. Social societies also often influence in daily life, in order to get a good relation and Islamic unity (ukhuwah islamiyah) inter-faith or other faiths. Based on the explanation above, the researcher whose thesis entitled “Education Aspects in the Holy Quran (An Analysis of Surah Makiyah)” formulates some statements of the problems; a) What kind of Education Aspects inside Q.S. An-Nahl: 106, Q.S.Al-Ankabut: 8, Q.S. Az-Zumar: 9, Q.S. Al-Kafirun:1-6, Q.S. Al-Ikhlas:1-4. b) How the Education Concept inside Q.S. An-Nahl: 106, Q.S.Al-Ankabut: 8, Q.S. Az-Zumar: 9, Q.S. Al-Kafirun:1-6, Q.S. Al-Ikhlas:1-4. The objective of the study is to find out the aspects and the concepts of Islamic education containing in the Q.S An Nahl: 106, Q.S Al Ankabut: 8, Q.S Az Zumar: 9, Q.S Al kafirun:1-6, and Q.S Al Ikhlas:1-4. This research includes in qualitative descriptive research inductively that statement inside several tafsir Al Quran refers to the research object of the theme. The analysis technique which researcher used in analyzing this research is Content Analysis Technique. It is a kind of scientific analysis about content or message of communication with some approaches; they are inductive and deductive in order to analyze the main data. The main data consists of Tafsir Al Misbah, Ibnu Katsir, Al Qurtubi, Al Aisar, Machmud Sakib, and Abuddin Nata which told about the interpretation of Q.S An Nahl: 106, Q.S Al Ankabut: 8, Q.S Az Zumar: 9, Q.S Al kafirun:1-6, and Q.S Al Ikhlas:1-4. The result of this research can be communicable that Q.S An Nahl: 106, Q.S Al Ankabut: 8, Q.S Az Zumar: 9, Q.S Al kafirun: 1-6, and Q.S Al Ikhlas: 1-4, have aspects and concepts of Islamic education as Islamic education materials which have to be learned. The aspects and concepts contain the belief of the unity of God which divided into three parts; tauhid rububiyah, tauhid uluhiyah and tauhid asma wa sifat. Then, it contains of behavior side which all Muslim have to have a good attitude or behavior towards their God, and Muslim moral to their parent. Also with society which can walked out with a good relation and Islamic unity either inter-faith or others faith. All those things have to be learned and taught to Muslim society in order to achieve insan kamil. Then, through the social society, Muslim can form a good Islamic unity either inter-faith or others faith. By banding four aspects of Islamic unity; ukhuwah islamiyah in ubudiyah, in insaniyah, in wathaniyah, and nasab wa dinul islam, peaceful can be born on this earth.